2013
DOI: 10.1093/aepp/ppt034
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Self‐control: Food Consumption, Physical Activity, and Weight‐loss Intention

Abstract: We find that despite a stronger intention to lose weight, overweight and obese individuals in the United States are less likely to meet the federal recommendations for fruit and vegetable consumption, energy and nutrient intakes, and physical activity than are normal‐weight individuals. By utilizing the Rotter score that measures self‐control capability, we find that obese individuals exhibit a lower degree of self‐control than normal‐weight individuals, and that this lack of self‐control is associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…Reducing the amount of daily kilocalories and fat grams consumed is essential for healthy weight loss (Lindström et al, 2006;Sacks et al, 2009), though decreasing dietary intake is known to be a substantial challenge (Fan & Jin, 2013;Glanz et al, 2005;Lillis, Hayes, Bunting, & Masuda, 2009;Tapper et al, 2009). In order to help people lose and maintain weight loss, effective interventions must address both psychological processes and key behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the amount of daily kilocalories and fat grams consumed is essential for healthy weight loss (Lindström et al, 2006;Sacks et al, 2009), though decreasing dietary intake is known to be a substantial challenge (Fan & Jin, 2013;Glanz et al, 2005;Lillis, Hayes, Bunting, & Masuda, 2009;Tapper et al, 2009). In order to help people lose and maintain weight loss, effective interventions must address both psychological processes and key behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Attention fatigue may occur when there is a need to focus on a specific stimulus or task with little or no intrinsically motivational draw, while suppressing distractions that may be inherently more interesting, with an example being filling in a tax return while your children are playing in the yard (Kaplan 1995;Kaplan and Berman 2010). Attentional fatigue is important, not least because it is associated with poorer decision making and lower levels of self-control, which in turn have been linked to a variety of healthrelated issues such as obesity via increasingly understood neural and behavioral pathways (Fan and Jin 2013;Hare, Camerer, and Rangel 2009;Vohs et al 2008). More than half the world's population lives in urban areas.…”
mentioning
confidence: 99%
“…Another possible explanation for the greater effectiveness of the anti-obesity advertisements on overweight individuals is associated with well-documented findings in the literature that overweight individuals tend to be more present biased and relatively lacking in self-control, especially in relation to dietary choices (Komlos, Smith, and Bogin 2004; Borghan and Golsteyn 2006; Zhang and Rashad 2008; Ikeda, Kang, and Ohtake 2010; Fan and Jin 2014). Advertising can affect individuals subconsciously through “visceral cues” (Laibson 2001), such as the sight and sound of food.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown that overweight individuals are more likely to be present-biased, which is to say they value immediate gratification over long-term benefit (O'Donoghue and Rabin 1999; Komlos, Smith, and Bogin 2004; Borghan and Golsteyn 2006; Fudenberg and Levine 2006; McClure et al 2007; Ikeda, Kang, and Ohtake 2010; Zhang and Rashad 2008). Relatedly, it has also been shown that overweight individuals have less self-control (Fan and Jin 2014). Therefore, it is reasonable to conjecture that overweight individuals might have different reactions to advertising content relative to individuals of normal weight.…”
Section: Introductionmentioning
confidence: 99%